Genetic risk factors associated with respiratory distress syndrome - Heui Seung Jo (Korean Pediatric Society, 2014)
Respiratory distress syndrome (RDS) among preterm infants is typically due to a quantitative deficiency of pulmonary surfactant. Aside from the degree of prematurity, diverse environmental and genetic factors can affect the development of RDS. The variance of the risk of RDS in various races/ethnicities or monozygotic/dizygotic twins has suggested genetic influences on this disorder. So far, several specific mutations in genes encoding surfactant-associated molecules have confirmed this. Specific genetic variants contributing to the regulation of pulmonary development, its structure and function, or the inflammatory response could be candidate risk factors for the development of RDS. This review summarizes the background that suggests the genetic predisposition of RDS, the identified mutations, and candidate genetic polymorphisms of pulmonary surfactant proteins associated with RDS.